Identification and analysis of Toll-related genes in the domesticated silkworm, Bombyx mori - Cheng, Ting-Cai; Zhang, Yu-Li; Liu, Chun; Xu, Ping-Zhen; Gao, Zhi-hong; Xia, Qing-You; Xiang, Zhong-Huai (Developmental and comparative immunology, 2008)
Silkworm ( Bombyx mori), a model system for Lepidoptera, has contributed enormously to the study of insect immunology especially in humoral immunity. But little is known about the molecular mechanism of immune response in the silkworm. Toll receptors are a group of evolutionarily ancient proteins, which play a crucial role in the innate immunity of both insects and vertebrates. In human, Toll-like receptors (TLRs) are the typical pattern recognition receptors for different kinds of pathogen molecules. Toll-related receptors in Drosophila, however, were thought to function as cytokine receptors in immune response and embryogenesis. We have identified 11 putative Toll-related receptors and two Toll analogs in the silkworm genome. Phylogenetic analysis of insect Toll family and human TLRs showed that BmTolls is grouped with Drosophila Tolls and Anopheles Tolls. These putative proteins are typical transmembrane receptors flanked by the extracellular leucine-rich repeat (LRR) domain and the cytoplasmic TIR domain. Structural prediction of the TIR domain alignment found five stranded sheets and five helices, which are alternatingly joined. Microarray data indicated that BmToll and BmToll-2 were expressed with remarkable enrichment in the ovary, suggesting that they might play a role in the embryogenesis. However, the enriched expression of BmToll-2 and -4 in the midgut suggested that the proteins they encode may be involved in immune defense. Testis-specific expression of BmToll-10 and -11 and BmToLK-2 implies that these may be involved in sex-specific biological functions. The RT-PCR results indicated that 10 genes were induced or suppressed with different degrees after their immune system was challenged by different invaders. Expression profiles of BmTolls and BmToLKs reported here provide insight into their role in innate immunity and development.